The role of macrophages in vascular calcification: strategies for diagnosis and treatment - Sheng, Yingkun; Qiu, Yue; Wang, Xiao; Shi, Jingyi; Yin, Ziyan; Zhang, Zile; Jiang, Shipeng; Zhang, Jian; Hu, Xiaoxiao; Hong, Weiling (Frontiers in Immunology, 2025)
Vascular calcification (VC) is an actively regulated pathological process that significantly increases the risk of cardiovascular events. As key cells of the innate immune system, macrophages play a dual role in VC through polarization into different phenotypes: Pro-inflammatory macrophages promote calcification by secreting pro-inflammatory factors, releasing apoptotic bodies, and producing extracellular vesicles (EVs); conversely, Anti-inflammatory macrophages inhibit calcification through anti-inflammatory factors, exosomes, plaque stabilization, and ATP/pyrophosphate (PPi) metabolism. However, under metabolic diseases such as diabetes, anti-inflammatory macrophages may exhibit pro-calcific properties. This review systematically summarizes the mechanisms of macrophage polarization in VC, discusses the application of macrophage-related biomarkers and imaging techniques in diagnosis, and highlights therapeutic strategies targeting macrophage polarization, recruitment, and activation. Finally, current challenges in dynamically monitoring macrophage polarization and context-dependent functional heterogeneity are outlined, and future research directions focusing on immunomodulation-based multi-target drug design and engineered cell therapies are proposed.